Structural characterization of polymeric nanofibers of polyvinylidene fluoride (PVDF) - Silva, José Augusto Souza Gomes Da; Silva, Walace Rodrigues Da [UNESP]; Silva, Ana Neilde Rodrigues Da; Künzel, Roseli; Bortoleto, José Roberto Ribeiro [UNESP]; Melo, Emanuel Benedito De; Ulsen, Carina; Trindade, Neilo Marcos (Associação Brasileira de Polímeros, 2023)
Polyvinylidene fluoride (PVDF) is a polymer material that exhibits piezoelectricity, which is the ability of certain materials to generate an electric charge in response to applied mechanical stress. Electrospun nanofibers were prepared from a solution with 1800 mg PVDF (18 wt.%) powder dissolved in 7.5 ml of dimethylformamide (DMF) and 2.5 ml acetone. The experimental setup used in the electrostatic deposition process was developed in our laboratory. Atomic Force Microscopy (AFM) showed that the fibers vary from 100 nm to 200 nm. Scanning Electron Microscopy (SEM) measurements showed distributed and well-formed nanofibers, but with few incidences of beads. The Energy Dispersive Spectroscopy (EDX) results showed that all points of the formed nanofibers have very similar chemical compositions, based on carbon and fluorine. Raman and Fourier Transform Infrared (FTIR) Spectroscopic analysis revealed the characteristic bands related to β-phase in the sample, which is responsible for the piezoelectricity of PVDF.
Keywords: beta phase; electrospinning; nanofibers; piezoelectricity